Geografias polifônicas : o perigo da história única na invenção do lugar - Silva, Vanessa Gusmão (2016)
Every year on May 23 there are a number of enactments which occur in commemoration of the holiday known as “Colonização do Solo Espírito Santense” (colonization of Espirito Santo soil) in the neighborhood of Prainha in Vila Velha/ES. Parades, exhibitions, catholic masses, theatrical plays combine, at the same time, a founding narrative: "Here began the history of Espirito Santo," "Vila Velha, the cradle of history". It is still possible to recognize the many reverberations of this colonial narrative, which express manners of speaking and acting in museums, monuments, symbols and rituals. In these discourses and practices, the "beginning of the history" always revolves around the arrival of the colonizers. This first observation echoes both poststructuralist and postcolonial studies, which have as one of their reflective fronts the questioning of metanarratives and unique histories-places in an effort of "denaturalization" of modern spatial narratives. Immersed within this perspective, our research seeks to analyze the consequences of a "politics of space" (MASSEY, 2008) when linked to the constitution of a Eurocentric linear spatial imagination. The agency of the memories and narratives of the place are discussed, having as reference authors like Doreen Massey (2007, 2008), Queiroz Filho (2010, 2012), Deleuze and Guattari (1977, 2011), Michel Pollak (1989), Benedict Anderson (2008) and Eduardo Pellejero (2009), whose conceptual motes allowed us to reflect over the fictional character of the narratives and images, as well as other possibilities of spelling and telling the places and their spatial imaginations. For this purpose, three methodological movements were conducted in this work. Firstly, a visual inventory of/at Prainha was performed, composed of a mapping of the narratives expressed by images and landscapes. In the second stage, we analyzed these narratives through an Assemblages Index, observing the power of territorialization or deterritorialization of these. Our intention was the tensing of the unique history-landscape of Prainha through a polyphonic geography, using erasure as a means of experiencing other manners of spelling it and telling it.